Physical and Mechanical Properties of Devitalized Xenografts Based on Pericardium, Aortic Valve Leaflets and Arteries - Mikhailova, Irina P.; Manchenko, Anna A.; Byzov, Denis V.; Sandomirsky, Boris P. (Problems of Cryobiology and Cryomedicine, 2015)
Physical and mechanical properties of the tissues of porcine pericardium, aortic valve leaflets and arteries have been studied following devitalization by cryoirradiation method. Low temperatures and ionizing radiation were used for pre-implantation treatment of xenotissues. Uniaxial tension of tissues was tested after freeze-thawing, radiation with flow of electrons, as well as after their combined impact. The extracellular matrix (ECM) of devitalized tissues has been shown to retain its integrity and to possess physical and mechanical properties characteristic for native tissue in both the longitudinal and transverse directions. Pre-freezing to –196°C exhibits a radioprotective effect and eliminates the negative influences of [beta–]-radiation on the ECM. Deep freezing and [beta–]-radiation induce the formation of additional intra- and intermolecular cross-linking as well as demonstrate a synergistic effect: elastic properties of tissues are significantly strengthened. Modified tissue of pericardium, valve leaflets and arteries with pre-determined physical and mechanical characteristics can be used as tissue implants and scaffolds: elastic properties provide lasting existence in a recipient's body (allowing the repopulation and formation of new structure); the strength margin to withstand the operational loads during functioning; preserved carcass ability, elasticity, extensibility, breakage and twisting resistance. Probl Cryobiol Cryomed 2015; 25(4):311-328.